First fatal HPAIV H5N1 (Clade 2.3.4.4B) infection in a domestic cat in Italy - D. D'Annunzio; M. Moreno; T. Tosi; B. Bassi; M. Muscatello; B. Bortolami; D. Drago; F. Fusaro; M. Monne; P. Palumbo; S. Savegnago; T. Terregino; et al. (Journal of Comparative Pathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Sheep abortions associated with Neospora caninum and Toxoplasma gondii infections in multiple flocks from Southern Brazil - Jéssica Aline Withoeft; Lucas Marian; Leonardo Silva da Costa; Fagner D’ambroso Fernandes; Fernanda Silveira Flores Vogel; Gabriela Bassi das Neves; Luiz Cláudio Miletti; Renata Assis Casagrande (Veterinary Research Communications, 2024)

Proposal of a reliable scoring system for the histological assessment of multiorgan injury in large animal models of ischaemia and shock - C. Palmieri; L. See Hoe; W. Dyer; S. Heinsar; S. Rozencwaig; J.P. Tung; N. Bartnikowski; M. Passmore; M. Bouquet; K. Hislop; E. Wilson; g. Li Bassi; et al. (Journal of Comparative Pathology, 2023)

Authentication of an Italian PDO hazelnut (“Nocciola Romana”) by NIR spectroscopy - Alessandra Biancolillo; Silvia De Luca; Sebastian Bassi; Léa Roudier; Remo Bucci; Andrea D. Magrì; Federico Marini (Environmental Science and Pollution Research, 2018)

Plant invasions on small Mediterranean islands: An overview - L. Celesti-Grapow; L. Bassi; G. Brundu; I. Camarda; E. Carli; G. D’Auria; E. Del Guacchio; G. Domina; G. Ferretti; B. Foggi; L. Lazzaro; P. Mazzola; et al. (Plant Biosystems, 2016)

Selecting with markers linked to the PPVres major QTL is not sufficient to predict resistance to Plum Pox Virus (PPV) in apricot - S. Decroocq; A. Chague; P. Lambert; G. Roch; J-M. Audergon; F. Geuna; R. Chiozzotto; D. Bassi; L. Dondini; S. Tartarini; J. Salava; B. Krška; et al. (Tree Genetics & Genomes, 2014)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Occurrence of TRGV-BJ hybrid gene in SV40-transformed fibroblast cell lines - L. P. G. D’Arce; C. L. Bassi; A. L. Fachin; G. A. S. Passos; E. T. Sakamoto-Hojo (Genetica, 2009)

Bitterness inheritance in apricot (P. armeniaca L.) seeds - P. Negri; D. Bassi; E. Magnanini; M. Rizzo; F. Bartolozzi (Tree Genetics & Genomes, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Plasticity of repetitive DNA in response to metal stress in Bryophytes - P. Bassi; A. Basile; M. Ferraro; M. Masi; D. Migliaccio; G. Morelli; E. Napolitano (Plant Biosystems, 2006)

A Zea mays 39-kDa thylakoid transglutaminase catalyses the modification by polyamines of light-harvesting complexII in a light-dependent way - M. Della Mea; A. Di Sandro; L. Dondini; S. Del Duca; F. Vantini; C. Bergamini; R. Bassi; D. Serafini-Fracassini (Planta, 2004)

Mutagenicity of Antineoplastic Drug Residues Treated in Health Care Waste Autoclave - M. D. Bassi; J. Moretton (Bulletin of Environmental Contamination and Toxicology, 2003)

Suborganellar localisation and effect of light on Helianthus tuberosus chloroplast transglutaminases and their substrates - L. Dondini; S. Del Duca; L. Dall'Agata; R. Bassi; M. Gastaldelli; M. Della Mea; A. Di Sandro; I. Claparols; D. Serafini-Fracassini (Planta, 2003)

Influence of River Water in the Detection of Cr(VI) Mutagenicity by the Ames Test - L. C. López; M. D. Bassi; J. Moretton (Bulletin of Environmental Contamination and Toxicology, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)